Health Education Using the Media Tool (Snakes and Ladders) on the Negative Impact of Gedget in SMP Negeri 1 Telaga Biru - Inne Ariane Gobel; Rona Febriona; Tias Rustam Nahu; Debby Mahdalena Yahya; Ferawati Monoarfa; Nur Meiliany Bouty; Octaviany Komendangi; Rianti Mile; Sri Indriati Ningsih Thalib; Sri Wahyuni Djibu; Sunatri F. Laliyo (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
Gadget is a term used to refer to several types of gadgetstechnological tools that are growing rapidly and have special functions.The objective of this health education is to reduce the negative impact of gadgets throughgame educational media. This service activity is carried out by givinginformation to junior high school students about the impact of gadgets, especially the negative impactgadgets on health as well as efforts to avoid the negative effects of gadgets,the service activities carried out are the preparation stage and the implementation stage. Based on the results of observations obtained after being given health education tostudents of SMP Negeri 1 TelagaBiru with a total of 10 students, the results showed the use of gadgets has an influence on social interaction, while for the process of10 people learn before and after health education is carried out on studentsby using a tool (Snakes and Ladders) on the negative impact of gadgetsThe results obtained are the gadget can affect the learning process, especially interest in learningstudent.